2019
DOI: 10.1177/2381468319881651
|View full text |Cite
|
Sign up to set email alerts
|

Communication and Shared Decision Making in the Breast Cancer Treatment Consultation: A Comparative Analysis of English- and Spanish-Speaking Patients

Abstract: Background. Communication in the breast cancer treatment consultation is complex. Language barriers may increase the challenge of achieving patient-centered communication and effective shared decision making. Design. We conducted a prospective cohort study among Spanish- and English-speaking women with stage 0 to 3 breast cancer in two urban medical centers in the Midwestern United States. Patient centeredness of care and decisional conflict were compared between Spanish- and English-speaking participants usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…This is consistent with work indicating that providers modify their risk discussions with patients with limited numeracy skills. 24 However, patients in our sample, the majority of whom scored incorrectly on numeracy items, identified risk information as a high priority for breast cancer SDM. Proven strategies may help overcome these expert and PCP-perceived numeracy-related barriers to sharing risk: Studies have shown precise risk estimates using decimals may be recalled less and perceived as less credible relative to an integer-based risk estimate.…”
Section: Discussionmentioning
confidence: 60%
“…This is consistent with work indicating that providers modify their risk discussions with patients with limited numeracy skills. 24 However, patients in our sample, the majority of whom scored incorrectly on numeracy items, identified risk information as a high priority for breast cancer SDM. Proven strategies may help overcome these expert and PCP-perceived numeracy-related barriers to sharing risk: Studies have shown precise risk estimates using decimals may be recalled less and perceived as less credible relative to an integer-based risk estimate.…”
Section: Discussionmentioning
confidence: 60%
“…Whitney et al suggested that trust can be enhanced through communication training or SDM tools that emphasise relational communication (Whitney et al, 2021). Interestingly, according to Pearson correlation analysis, MHPs' discrimination had significant correlation with SDM practices, but it did not show significance in the multiple linear regression analysis, which is inconsistent with previous studies and the hypotheses (Schapira et al, 2019;Whitney et al, 2021). More researches are still needed to explore whether MHPs' discrimination towards consumers affects their practices and perceptions of SDM in the daily management of adolescents diagnosed with depression and the specific reasons (Altman et al, 2019;Progovac et al, 2020).…”
Section: Working In Closed and Open Inpatient Mental Health Wards Maymentioning
confidence: 82%
“…Research has shown that strong consumer‐provider alliances built on trust and mutual respect are essential for healthcare providers to understand, incorporate and consistently respect consumers' treatment preferences (Whitney et al., 2021). Consumers exposed to discrimination may face significant challenges in building trusting relationships with providers and participating in the SDM process (Schapira et al., 2019; Whitney et al., 2021). However, few studies have investigated whether MHPs' trust, discrimination and preference influence their SDM practices for adolescents diagnosed with depression.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown a lack of clarity in communication for NES Latina patients during their breast cancer consultations; this issue is a potential target for addressing delays after diagnosis. 39 In addition, successful patient navigation, including coordinating appointments, transportation, telephone support, interpretation, and assistance with insurance paperwork, is another target that has been shown to decrease delays in breast cancer treatment. 40 The influence of language on delays in breast cancer care is particularly important in the United States, where the use of languages other than English increased by 148% from 1980 to 2009, especially Spanish, Vietnamese, and Russian.…”
Section: Discussionmentioning
confidence: 99%